Analysis of chemotypes and their markers in leaves of core collections of Eucommia ulmoides using metabolomics - Meng, Yide; Du, Qingxin; Du, Hongyan; Wang, Qi; Wang, Lu; Du, Lanying; Liu, Panfeng (Frontiers in Plant Science, 2023)
The leaves of Eucommia ulmoides Oliver contain various active substances and nutritional components. They have been included in the Chinese Pharmacopoeia, the Health Food Raw Material Catalogue, and the Feed Raw Material Catalogue as raw materials for Traditional Chinese Medicine. Core collections has been constructed from conserved germplasm resources based on molecular markers and some morphological indicators. However, there is limited information regarding the metabolic characteristics of the E. ulmoides core germplasm population. This study aims to comprehensively characterize the metabolite profile of E. ulmoides core collections leaves. 193 core collections of E. ulmoides were analyzed using non-targeted metabolomic techniques and MS-DIAL pretreatment of the leaves of E. ulmoides mass spectrometry data was determined and combined with RF signal correction. The gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) metabolomic data were annotated with 208 and 892 metabolites, respectively. 120 key herbal chemical components were screened and 85 disease-resistant metabolites were identified. The core collections leaves of E. ulmoides were classified into four chemotypes using self-organizing map (SOM) clustering. 103 differential markers were screened, among which, 30, 23, 43, and 23 markers corresponded to chemotypes I, II, III, and IV, respectively. The weighted gene co-expression network analysis (WGCNA) was done. Due to the correlation between differential markers and morphological traits in each module leaf length, chlorophyll reference value, leaf dentate height, and leaf thickness were determined as the characteristic traits of chemotypes I, II, III, and IV, respectively. The constructed random forest (RF) model with flavonoid and phenylpropanoid metabolites could distinguish different chemotypes of E. ulmoides populations. Interestingly, the flavonoid metabolites showed an overall highly significant negative correlation with leaf length, leaf area, and leaf circumference, where flavonols (quercetin-3-O-pentosidine, quercetin-3-O-glucoside) could be used as common markers for leaf length, leaf area, and leaf circumference.